One-bead-one-compound screening approach to the identification of cyclic peptoid inhibitors of cyclophilin D as neuroprotective agents from mitochondrial dysfunction. Issue 19 (4th February 2021) - Hyun, Soonsil; Park, Namjoon; Nam, So Hee; Cheon, Dae Hee; Lee, Yan; Lim, Hyun-Suk; Yu, Jaehoon
Abstract : The novel cyclic peptoid I11, identified from the OBOC library, promotes recovery of damaged mitochondria via binding to CypD, rejuvenating mitochondrial function without toxicity. Abstract : In an effort designed to discover superior inhibitors of cyclophilin D (CypD), we identified and screened members of a one-bead-one-compound (OBOC) library of cyclic peptoid analogues of cyclosporin A (CsA). The results show that the one member of this cyclic peptoid family, I11, inhibits mitochondrial membrane potential changes mediated by CypD.